Nanofiber with core-shell structure, diaphragm, preparation method of nanofiber and preparation method of diaphragm, and battery

By covering ceramic particles on the core surface of the polymer fibers of the lithium-ion battery separator and forming a shell, nanofibers with core-shell structure are constructed, which solves the problem of deformation of the existing separator at high temperatures, and achieves higher high-temperature deformation resistance and battery safety performance.

CN119710973APending Publication Date: 2025-03-28CHONGQING TALENT NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411353398.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators affect the safety performance of the battery due to shrinkage at high temperatures. The existing methods such as coating inorganic ceramic materials have problems with poor interface contact, making it difficult to effectively improve the high-temperature deformation resistance of the separators.

Method used

Nanofibers with core-shell structure are used to form a shell by covering ceramic particles on the surface of the core of the polymer fiber and connecting them through the second polymer to form a separator with good resistance to high temperature deformation.

Benefits of technology

It improves the high-temperature deformation resistance of the diaphragm, maintains its original shape at high temperature, avoids large-area contact between positive and negative electrodes, improves the safety performance of lithium-ion batteries, and has a certain degree of flexibility, suitable for flexible devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710973A_ABST
    Figure CN119710973A_ABST
Patent Text Reader

Abstract

The invention discloses a nanofiber with a core-shell structure, a diaphragm, a preparation method of the nanofiber and a battery. The nanofiber with the core-shell structure comprises a polymer fiber core and a shell covering the surface of the polymer fiber core, a polymer in the polymer fiber core comprises a first polymer, and the shell comprises a second polymer and ceramic particles. According to the nanofiber with the core-shell structure, the surface of the polymer fiber core is covered with the ceramic particles, the ceramic particles are connected together through the second polymer to form the shell, and the high-temperature deformation resistance of the polymer fiber can be well improved. The diaphragm formed by the nanofibers with the core-shell structure has good high-temperature deformation resistance and can well maintain the original shape at high temperature, and the purpose of improving the safety of the lithium ion battery is achieved. In addition, the diaphragm formed by the nanofibers with the core-shell structure has certain flexibility and can be applied to the field of flexible devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a nanofiber with a core-shell structure, a diaphragm, a preparation method thereof, and a battery. Background Art

[0002] At present, most commercial separators are made of polyethylene separators or polyethylene separators, which have certain strength and high temperature resistance and are widely used in the field of lithium-ion batteries. However, the melting point of polyethylene is 112°C and the melting point of polypropylene is about 165°C, which makes the polyethylene separator and polypropylene separator shrink when the battery is in extreme conditions such as high temperature, which affects the safety performance of the battery.

[0003] The commonly used method in the prior art is to coat inorganic ceramic materials on both sides of a polyethylene diaphragm or a polypropylene diaphragm to form a ceramic composite diaphragm, and utilize the heat resistance of inorganic ceramics to improve the ability of the diaphragm to resist high-temperature deformation. However, combining the two by coating may result in poor interface contact, affecting the improvement of its ability to resist high-temperature deformation.

[0004] Therefore, providing a material suitable for the preparation of diaphragms so that the ability of the diaphragms prepared using the material to resist high-temperature deformation is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a nanofiber with a core-shell structure, a diaphragm, a preparation method thereof and a battery.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a nanofiber with a core-shell structure, wherein the nanofiber with a core-shell structure comprises a polymer fiber core and a shell coated on the surface of the polymer fiber core, the polymer in the polymer fiber core comprises a first polymer, and the shell comprises a second polymer and ceramic particles.

[0008] The present invention provides a nanofiber with a core-shell structure, in which the surface of the inner core of the polymer fiber is covered with ceramic particles, and the ceramic particles are connected together by a second polymer to form an outer shell, which can well improve the ability of the polymer fiber to resist high-temperature deformation. The diaphragm formed by the nanofiber with a core-shell structure has good high-temperature deformation resistance. At high temperatures (such as when the battery is short-circuited), it can well maintain the original shape and avoid contact between the positive and negative extreme areas to achieve the purpose of improving the safety of lithium-ion batteries. Moreover, the diaphragm formed by the nanofiber with a core-shell structure has a certain flexibility and can be applied to the field of flexible devices.

[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0010] Preferably, based on the total mass of the core-shell structured nanofibers as 100%, the mass of the polymer fiber core accounts for 50%-70%, for example, 50%, 53%, 55%, 57%, 60%, 62%, 65%, 68% or 70%.

[0011] Preferably, in the polymer fiber core, the first polymer includes at least one of polyethylene (PE) and polypropylene (PP).

[0012] Preferably, based on the total mass of the nanofibers with a core-shell structure as 100%, the mass of the shell accounts for 30%-50%, for example, 30%, 32%, 35%, 37%, 38%, 40%, 43%, 46% or 50%.

[0013] Preferably, in the shell, the second polymer includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), polymethyl methacrylate (PMMA), polyacrylic acid (PAA), polyacrylonitrile (PAN), perfluorosulfonic acid resin (Nafion-H), perfluorosulfonic acid resin lithium (Nafion-Li), thermoplastic polyurethane (TPU), polyphenylene sulfide (PPS), polyethyleneimine, polyethyl cyanoacrylate (PCA), polyvinyl carbonate (PEC), polypropylene carbonate (PPC), polyvinyl carbonate (PVC), polymalonate substances, polysuccinate substances, polyimide (PI), polyetherimide and polyethersulfone (PESU).

[0014] Preferably, the polymalonate material includes at least one of polypentylene malonate (PPM), polyethylene malonate (PEM), polypropylene malonate (PTM) and polyhexylene malonate (PHM).

[0015] Preferably, the polysuccinate-based material includes at least one of polyethylene succinate (PES) and propylene succinate.

[0016] Preferably, based on the total mass of the shell as 100%, the mass content of the second polymer is 90%-20%, for example, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25% or 20%, etc., preferably 50%-40%.

[0017] Preferably, the ceramic particles are located on the surface and / or inside of the shell.

[0018] Preferably, based on the total mass of the shell being 100%, the mass content of the ceramic particles is 10%-80%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc., preferably 50%-60%. If there are too few ceramic particles in the shell, the high temperature deformation resistance of the diaphragm will be reduced; if there are too many ceramic particles in the shell, the ceramic will cover the outer wall of the inner core, hindering the penetration of the electrolyte.

[0019] Preferably, in the shell, the ceramic particles include a first inorganic ceramic, and the first inorganic ceramic is a nitride inorganic ceramic.

[0020] In addition to good insulation, nitride inorganic ceramics also have excellent high temperature resistance and thermal conductivity. When used in diaphragms, they can effectively improve the diaphragm's ability to resist high temperature deformation and improve the safety performance of the battery. Taking cubic boron nitride as an example, it has an extremely high melting point, excellent thermal shock resistance, thermal stress resistance, and good shrinkage resistance at high temperatures. It also has good thermal conductivity and can transfer heat to other parts in a shorter time. Therefore, it can play a good supporting role in the diaphragm at high temperatures, avoiding battery short circuits caused by deformation of the diaphragm, improving the diaphragm's resistance to high temperature shrinkage, and ensuring the battery's high temperature safety performance. Moreover, nitride inorganic ceramics have a lower density, which can maximize the control of the overall quality of the battery.

[0021] Preferably, the nitride inorganic ceramic includes at least one of boron nitride, aluminum nitride, silicon nitride, titanium nitride and magnesium nitride.

[0022] Preferably, the boron nitride includes hexagonal boron nitride and / or N-type cubic boron nitride.

[0023] Preferably, the inorganic ceramic also includes a second inorganic ceramic, and the second inorganic ceramic includes at least one of aluminum oxide, titanium dioxide, silicon dioxide, zirconium dioxide, molybdenum-doped silicon dioxide, zirconium boride, zirconium nitride ceramics, silicon boride, vanadium boride, titanium boride, magnesium boride and an inorganic ceramic solid electrolyte.

[0024] Preferably, the inorganic ceramic solid electrolyte includes at least one of lithium lanthanumzirconium oxide (LLZO), lithium lanthanum titanate oxide (LLTO), tantalum-doped lithium lanthanum zirconium oxide (LLZTO), aluminum-doped lithium lanthanum zirconium oxide (LLZAO), lithium germanium phosphorous sulfide (LGPS), lithium phosphorous sulfur chloride (LPSCl) and lithium aluminum germanium phosphate (LAGP).

[0025] Preferably, the mass of the second inorganic ceramic accounts for 0-95% of the mass of the first inorganic ceramic and does not contain 0%, for example, 0.05%, 0.1%, 0.5%, 1%, 3%, 5%, 7%, 10%, 12.5%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 33%, 36%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%, etc.

[0026] As a preferred technical solution of the nanofiber with core-shell structure described in the present invention, the shell also includes a one-dimensional material toughening agent. By adding the one-dimensional material toughening agent, the toughness of the shell can be increased, and the mechanical properties of the nanofiber with core-shell structure can be improved.

[0027] Preferably, in the shell, the mass ratio of the one-dimensional material toughening agent to the ceramic particles is 1:(5-10), for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:9.5 or 1:10, etc.

[0028] Preferably, the one-dimensional material toughening agent is selected from at least one of a one-dimensional inorganic material and a one-dimensional organic material.

[0029] Preferably, the one-dimensional inorganic material includes at least one of aluminum oxide fiber, silicon dioxide fiber, zirconium dioxide fiber, boron nitride fiber, boron nitride nanotube, glass fiber, titanium dioxide nanotube and zirconium dioxide nanotube.

[0030] Preferably, the mass proportion of the one-dimensional inorganic material in the one-dimensional material toughening agent is 50%-100%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc. Among them, the mass proportion of the one-dimensional inorganic material in the one-dimensional material toughening agent is 100%, which means that the one-dimensional material toughening agent is all one-dimensional inorganic material.

[0031] Preferably, the one-dimensional organic material includes at least one of nylon fiber, polyvinylidene fluoride fiber, polyimide fiber, polyphenylene sulfide fiber, polyvinylidene fluoride-hexafluoropropylene fiber and polyvinylidene fluoride-chlorotrifluoroethylene fiber.

[0032] Preferably, the mass proportion of the one-dimensional organic material in the one-dimensional material toughening agent is 0%-50%, for example, 0%, 0.05%, 0.1%, 0.5%, 1%, 3%, 5%, 7%, 10%, 12.5%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 33%, 36%, 40%, 45% or 50%, etc. Among them, the mass proportion of the one-dimensional organic material in the one-dimensional material toughening agent is 0%, which means that the one-dimensional material toughening agent does not contain one-dimensional organic material.

[0033] By selecting one-dimensional inorganic materials or one-dimensional organic materials with high temperature resistance, they can resist deformation under high temperature, further ensuring the high temperature resistance and high strength of the composite diaphragm. At the same time, in coordination with the ceramic particles in the shell, a more stable structure can be built, improving the high temperature deformation resistance of the nanofibers with core-shell structure.

[0034] Preferably, the diameter of the nanofibers with a core-shell structure is 1 μm-5 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.3 μm, 3.6 μm, 4 μm, 4.3 μm, 4.5 μm or 5 μm.

[0035] Preferably, the diameter of the polymer fiber core is 500 nm-2 μm, for example, 500 nm, 600 nm, 800 nm, 1 μm, 1.2 μm, 1.3 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm or 2 μm.

[0036] Preferably, the particle size of the ceramic particles is 10nm-500nm, such as 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 325nm, 335nm, 360nm, 380nm, 400nm, 425nm, 450nm, 475nm or 500nm, etc., preferably 50nm-300nm. If the particle size of the ceramic particles is too small, agglomeration is likely to occur; if the particle size of the ceramic particles is too large or even exceeds the diameter of the polymer fiber core, the ceramic particles are likely to fall off, which is not conducive to forming a membrane material with a relatively uniform pore size.

[0037] In a second aspect, the present invention provides a method for preparing a nanofiber having a core-shell structure as described in the first aspect, the method comprising the following steps:

[0038] dissolving a first polymer in a first organic solvent to obtain a solution A;

[0039] adding a second polymer and ceramic particles into a second organic solvent to obtain a dispersion B;

[0040] Among them, the preparation of solution A and dispersion B is in no particular order;

[0041] Solution A and dispersion B are used to prepare the nanofibers with a core-shell structure by using a coaxial electrospinning method or a melt-blowing method.

[0042] The method of the present invention utilizes coaxial electrospinning or melt-blowing to prepare nanofibers of core-shell structure, which can tightly bind ceramic particles to the surface of polymer fibers and improve the interface bonding between the two. Moreover, the method can directly obtain a diaphragm with high strength and strong high-temperature deformation resistance.

[0043] Among them, the working principle of the electrospinning process is that the microparticles in the solution are pulled by the force of the electrostatic field, and the microparticles in the solution are dispersed into nano-scale filaments by the force of the electrostatic field, thereby preparing nanofibers with a core-shell structure. The melt-blowing method is different from the electrospinning process. The melt-blowing method relies on the impact of high-speed gas to make the polymer solution or solution draw, orient, and form holes) to prepare nanofibers with a core-shell structure.

[0044] Preferably, the first organic solvent comprises at least one of toluene, benzene, chloroform, paraffin, petroleum ether and mineral oil.

[0045] Preferably, during the preparation of solution A, the temperature is raised to above 70°C during dissolution, for example, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 97°C.

[0046] Preferably, the second organic solvent includes at least one of nitrogen methyl pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, acetone and ethanol.

[0047] Preferably, during the preparation of the dispersion B, the material added to the second organic solvent also includes a one-dimensional material toughening agent.

[0048] As a preferred technical solution of the method for preparing the nanofibers with a core-shell structure of the present invention, when the nanofibers with a core-shell structure are prepared by a coaxial electrospinning method or a melt-blowing method, the dew point of the environment is less than -30°C;

[0049] Preferably, during the coaxial electrospinning process, the voltage range is 5 kV-22 kV, for example, 5 kV, 8 kV, 10 kV, 12 kV, 15 kV, 16 kV, 18 kV, 20 kV or 22 kV.

[0050] Preferably, during the coaxial electrospinning process, the distance from the receiving plate to the needle is 13 cm-25 cm, for example, 13 cm, 14 cm, 15 cm, 17 cm, 18 cm, 20 cm, 21 cm, 23 cm or 25 cm.

[0051] In the present invention, the coaxial electrospinning method is carried out as follows: solution A and dispersion B are injected into the syringe of the coaxial electrospinning device, a voltage is applied between the needle of the syringe and the receiving plate, the slurry is ejected from the needle and a membrane material is formed on the receiving plate. If the distance from the receiving plate to the needle is too small, the formed membrane material will carry excess solvent, causing the fibers to entangle with each other; if the distance from the receiving plate to the needle is too large, the solvent will evaporate completely, causing the membrane material to fall off and unable to form.

[0052] In a third aspect, the present invention provides a diaphragm, which is formed by the nanofibers with a core-shell structure as described in the first aspect, or is prepared by the method as described in the second aspect.

[0053] The present invention forms nanofibers with a core-shell structure by a coaxial electrospinning method or a melt-blowing method. These nanofibers with a core-shell structure then form a diaphragm, or the nanofibers with a core-shell structure are directly formed in the process of preparing the diaphragm. This is different from the prior art of forming a diaphragm and then coating the nanofibers. In the present invention, the ceramic particles can be tightly combined with the surface and / or the inside of the outer shell of the polymer fiber, so that the high-temperature deformation resistance of the diaphragm formed by the nanofibers is significantly improved.

[0054] In a fourth aspect, the present invention provides a battery, comprising a positive electrode, a negative electrode and a separator, wherein the separator is located between the positive electrode and the negative electrode to isolate the positive electrode from the negative electrode, and the separator is the separator described in the third aspect.

[0055] Preferably, the battery is an all-solid-state battery or a semi-solid-state battery.

[0056] Preferably, a flexible interface is formed between the separator and the positive electrode and / or between the separator and the negative electrode.

[0057] The present invention utilizes the high elasticity of the polymer to make the part of the separator in direct contact with the positive and negative electrodes have good compatibility, improve the interface performance of the battery, effectively reduce the interface resistance, and avoid the problem of interface difference caused by direct contact between the ceramic particles and the positive and negative electrodes. The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] The present invention provides a nanofiber with a core-shell structure, in which the surface of the inner core of the polymer fiber is covered with ceramic particles, and the ceramic particles are connected together by a second polymer to form an outer shell, which can well improve the ability of the polymer fiber to resist high-temperature deformation. The diaphragm formed by the nanofiber with a core-shell structure has good high-temperature deformation resistance. At high temperatures (such as when the battery is short-circuited), it can well maintain the original shape and avoid contact between the positive and negative extreme areas to achieve the purpose of improving the safety of lithium-ion batteries. Moreover, the diaphragm formed by the nanofiber with a core-shell structure has a certain flexibility and can be applied to the field of flexible devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 1 is a schematic diagram of the structure of a nanofiber with a core-shell structure in one embodiment of the present invention, wherein 1 is a polymer fiber core, 2 is an outer shell, and 21 is a ceramic particle. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0062] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0063] Example 1

[0064] A nanofiber with a core-shell structure, the structural schematic diagram is as follows Figure 1As shown, it comprises a polymer fiber core 1 and a shell 2 coated on the surface of the polymer fiber core 1, wherein the polymer fiber core 1 is a polyethylene (PE) core, and the shell 2 comprises polyethylene oxide (PEO) and ceramic particles 21, and the ceramic particles 21 are hexagonal boron nitride;

[0065] Wherein, taking the total mass of the nanofiber with a core-shell structure as 100%, the mass of the core of the polymer fiber accounts for 60%, and the mass of the shell accounts for 40%;

[0066] Based on the total mass of the shell being 100%, the mass content of the ceramic particles is 50%, and the mass content of PEO is 50%;

[0067] The diameter of the nanofiber with a core-shell structure is 2 μm, the diameter of the core of the polymer fiber is 1 μm, and the particle size of the ceramic particles is 100 nm.

[0068] The method for preparing the nanofibers with a core-shell structure provided in this embodiment comprises the following steps:

[0069] Add PE to benzene and heat to 75°C to obtain solution A;

[0070] PEO and ceramic particles (hexagonal boron nitride) are added to nitrogen methyl pyrrolidone (NMP) to obtain dispersion B;

[0071] Under the condition of an environmental dew point of -40°C, solution A and dispersion B were used to prepare a diaphragm containing nanofibers with a core-shell structure by a coaxial electrospinning method. The coaxial electrospinning method was specifically carried out as follows: solution A and dispersion B were injected into the syringe of a coaxial electrospinning device, a voltage was applied between the needle of the syringe and a receiving plate, slurry was ejected from the needle and a membrane material (i.e., a diaphragm) was formed on the receiving plate, wherein the voltage was 10 kV and the distance from the receiving plate to the needle was 20 cm.

[0072] A diaphragm is prepared by the above preparation method.

[0073] Example 2

[0074] A nanofiber with a core-shell structure, comprising a polymer fiber core and a shell coated on the surface of the polymer fiber core, wherein the polymer fiber core is a polypropylene (PP) core, and the shell comprises polyvinylidene fluoride (PVDF) and ceramic particles, wherein the ceramic particles are N-type cubic boron nitride;

[0075] Wherein, taking the total mass of the nanofiber with a core-shell structure as 100%, the mass of the core of the polymer fiber accounts for 55%, and the mass of the shell accounts for 45%;

[0076] Taking the total mass of the shell as 100%, the mass content of the ceramic particles is 60%, and the mass content of the PVDF is 40%;

[0077] The diameter of the nanofiber with a core-shell structure is 5 μm, the diameter of the core of the polymer fiber is 2 μm, and the particle size of the ceramic particles is 300 nm.

[0078] The method for preparing the nanofibers with a core-shell structure provided in this embodiment comprises the following steps:

[0079] Add PP to toluene and heat to 80°C to obtain solution A;

[0080] Adding PVDF and ceramic particles (N-type cubic boron nitride) into acetonitrile to obtain dispersion B;

[0081] Under the condition of an environmental dew point of -35°C, solution A and dispersion B were used to prepare a diaphragm containing nanofibers with a core-shell structure by a coaxial electrospinning method. The coaxial electrospinning method was specifically carried out as follows: solution A and dispersion B were injected into the syringe of a coaxial electrospinning device, a voltage was applied between the needle of the syringe and a receiving plate, slurry was sprayed out of the needle and a membrane material was formed on the receiving plate, wherein the voltage was 20 kV and the distance from the receiving plate to the needle was 15 cm.

[0082] A diaphragm is prepared by the above preparation method.

[0083] Example 3

[0084] A nanofiber with a core-shell structure, comprising a polymer fiber core and a shell coated on the surface of the polymer fiber core, wherein the polymer fiber core is a polyethylene (PE) core, and the shell comprises polyacrylonitrile (PAN) and ceramic particles;

[0085] The ceramic particles include a first inorganic ceramic and a second inorganic ceramic, the first inorganic ceramic is aluminum nitride, the second inorganic ceramic is silicon dioxide, and the mass of the second inorganic ceramic accounts for 30% of the mass of the first inorganic ceramic;

[0086] Taking the total mass of the nanofiber with a core-shell structure as 100%, the mass of the core of the polymer fiber accounts for 65%, and the mass of the shell accounts for 35%;

[0087] Based on the total mass of the shell being 100%, the mass content of the ceramic particles is 55%, and the mass content of PAN is 45%;

[0088] The diameter of the nanofiber with a core-shell structure is 1.5 μm, the diameter of the core of the polymer fiber is 500 nm, and the particle size of the ceramic particles is 50 nm.

[0089] The method for preparing the nanofibers with a core-shell structure provided in this embodiment comprises the following steps:

[0090] Add PE to chlorobenzene and heat to 90°C to obtain solution A;

[0091] PAN and ceramic particles (aluminum nitride and silicon dioxide) were added to ethanol to obtain dispersion B;

[0092] Under the condition of an environmental dew point of -45°C, solution A and dispersion B were used to prepare a diaphragm including nanofibers with a core-shell structure by a melt-blowing method.

[0093] A diaphragm is prepared by the above preparation method.

[0094] Example 4

[0095] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differs from Example 1 in that, in the preparation method, the ceramic particles are replaced by a mixture of nylon fibers and ceramic particles in a mass ratio of 1:7. Through the above method, in the nanofiber with a core-shell structure, based on the total mass of the shell as 100%, the total mass content of the nylon fibers and the ceramic particles is 50%, and the mass content of PEO is 50%.

[0096] Example 5

[0097] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differs from Example 1 in that, in the preparation method, the ceramic particles are replaced by a mixture of glass fibers and ceramic particles in a mass ratio of 1:9. By adjusting the above method, in the nanofiber with a core-shell structure, based on the total mass of the shell being 100%, the total mass content of the glass fibers and the ceramic particles is 50%, and the mass content of PEO is 50%.

[0098] Example 6

[0099] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differ from Example 1 in that the amount of ceramic particles added in the preparation method is changed so that in the nanofiber with a core-shell structure, the mass content of the ceramic particles is 40%, and the mass content of PEO is 60%, based on the total mass of the shell being 100%.

[0100] Example 7

[0101] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differ from Example 1 in that the amount of ceramic particles added in the preparation method is changed so that in the nanofiber with a core-shell structure, the mass content of the ceramic particles is 70%, and the mass content of PEO is 30%, based on the total mass of the shell being 100%.

[0102] Example 8

[0103] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differs from Example 1 in that the amount of PE added in the preparation method is changed so that in the nanofiber with a core-shell structure, the mass of the polymer fiber core accounts for 40% based on the total mass of the nanofiber with a core-shell structure as 100%. Accordingly, the diameter of the nanofiber with a core-shell structure is 1.4 μm, and the diameter of the polymer fiber core is 400 nm.

[0104] Example 9

[0105] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differ from Example 1 in that the amount of PE added in the preparation method is changed so that in the nanofiber with a core-shell structure, the mass of the polymer fiber core accounts for 80% based on the total mass of the nanofiber with a core-shell structure as 100%. Accordingly, the diameter of the nanofiber with a core-shell structure is 3.1 μm, and the diameter of the polymer fiber core is 2.2 μm.

[0106] Example 10

[0107] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differ from Example 1 in that the particle size of the ceramic particles in the preparation method is changed so that the particle size of the ceramic particles in the nanofiber with a core-shell structure is 30 nm.

[0108] Embodiment 11

[0109] A nanofiber with a core-shell structure, a diaphragm and a preparation method thereof, which differ from Example 1 in that the particle size of the ceramic particles in the preparation method is changed so that the particle size of the ceramic particles in the nanofiber with a core-shell structure is 320nm.

[0110] Comparative Example 1

[0111] A nanofiber, a diaphragm and a preparation method thereof, which differ from Example 1 in that no ceramic particles are added in the preparation method, so that the nanofiber does not contain ceramic particles.

[0112] Application Example 1

[0113] A lithium ion battery comprises a positive electrode, a negative electrode, a separator (Example 1) and an electrolyte, and a method for preparing the lithium ion battery comprises the following steps:

[0114] According to the mass ratio of lithium iron phosphate (LFP): Super P: PVDF = 8:1:1, LFP, Super P and PVDF were dispersed in NMP, and the solid content was controlled to 60% to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil with a scraper with a thickness of 100 μm and dried for standby use.

[0115] The electrolyte composition is: 1 mol / L LiPF 6 The electrolyte was EC:DMC (volume ratio) = 1:1 mixture as the solvent.

[0116] A lithium sheet with a thickness of 100 μm was used as the counter electrode and a button cell of model 2032 was assembled in an inert gas glove box with a water and oxygen content of less than 0.1 ppm.

[0117] Application Example 2-11

[0118] A lithium ion battery is different from Application Example 1 only in that the diaphragm of Example 1 is replaced by the diaphragms of Examples 2-11 respectively.

[0119] Application Comparative Example 1

[0120] A lithium ion battery, which is different from Application Example 1 only in that the diaphragm of Example 1 is replaced by the diaphragm of Comparative Example 1.

[0121] Performance Test:

[0122] (1) Thermal shrinkage of the diaphragm: The diaphragm was placed in an oven at 150°C for 1 hour and then taken out. The size of the sample before and after heating was recorded. The thermal shrinkage was calculated by the area change. The calculation formula is: Thermal shrinkage = (S 0 -S 1 ) / S 0 × 100%, where S 0 is the area before heating, S 1 is the area after heating.

[0123] (2) Capacity retention rate of lithium-ion batteries: At room temperature, charge and discharge cycles were performed for 100 cycles at a current density of 0.1C and a voltage range of 2.5V-3.65V. The capacity retention rate after 100 cycles was calculated using the following formula: Capacity retention rate = C 100 / C 1 × 100%, where C 100 is the discharge capacity at the 100th cycle, C 1 is the discharge capacity of the first cycle.

[0124] The thermal shrinkage rate and capacity retention rate of the diaphragms of Examples 1-11 and Comparative Example 1 were tested according to the above test method. The test results are shown in Table 1.

[0125] Table 1

[0126]

[0127] It can be seen from the above embodiments, application examples and Table 1 that the present invention can effectively improve the strength and high temperature deformation resistance of the diaphragm by coating the surface of the polymer fiber with a shell containing ceramic particles and a polymer to form a diaphragm, and can effectively improve the safety performance of the battery. Since the diaphragm used in Comparative Example 1 does not contain ceramic particles on the surface of the polymer fiber, the strength and high temperature deformation resistance are reduced, and the capacity retention rate of the lithium ion battery assembled with the diaphragm of Comparative Example 1 after 100 cycles is reduced from 93.48% in Example 1 to 83.59%.

[0128] At the same time, through the comparison between Example 1 and Example 4-5 and between Application Example 1 and Application Example 4-5, it can be seen that by using ceramic particles and one-dimensional material toughening agents in the outer shell of the core-shell structured nanofibers, the high-temperature deformation resistance of the diaphragm can be further improved, thereby improving the cycle performance of the lithium-ion battery.

[0129] By comparing Application Example 1 with Application Examples 6-7, it can be seen that there is an optimal range for the mass ratio of ceramic particles and polymer in the shell of the core-shell structured nanofiber. If there are too few ceramic particles in the shell, the high-temperature deformation resistance of the diaphragm will be reduced; if there are too many ceramic particles in the shell, the ceramic will cover the outer wall of the inner core, hindering the penetration of the electrolyte.

[0130] By comparing Application Example 1 with Application Examples 8-9, it can be seen that in the nanofibers with a core-shell structure, the mass proportion of the polymer core in the nanofibers with a core-shell structure has an optimal range. If the mass proportion of the polymer core is too low, the ceramic content of the shell will be high, affecting the permeability of the electrolyte; if the mass proportion of the polymer core is too high, the ceramic content of the shell will be low, affecting the high temperature resistance of the diaphragm.

[0131] By comparing Application Example 1 with Application Examples 10-11, it can be seen that in the outer shell of the core-shell structured nanofiber, there is an optimal range for the particle size of the ceramic particles. If the particle size of the ceramic particles is too small, agglomeration will occur, and uniform distribution of the particles cannot be achieved. The inner core material without particle coverage will be greatly affected by high temperature. If the particle size of the ceramic particles is too large, the ceramic particles will fall off, which is not conducive to the formation of a membrane material with a relatively uniform pore size.

[0132] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A nanofiber having a core-shell structure, characterized in that: The nanofiber with a core-shell structure comprises a polymer fiber core and a shell coated on the surface of the polymer fiber core, the polymer in the polymer fiber core comprises a first polymer, and the shell comprises a second polymer and ceramic particles.

2. The nanofiber with a core-shell structure according to claim 1, characterized in that: Taking the total mass of the nanofibers with a core-shell structure as 100%, the mass of the core of the polymer fiber accounts for 50%-70%; Preferably, in the polymer fiber core, the first polymer comprises at least one of polyethylene and polypropylene; Preferably, based on the total mass of the nanofibers having a core-shell structure being 100%, the mass of the shell accounts for 30%-50%; Preferably, in the shell, the second polymer includes at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polymethyl methacrylate, polyacrylic acid, polyacrylonitrile, perfluorosulfonic acid resin, perfluorosulfonic acid resin lithium, thermoplastic polyurethane, polyphenylene sulfide, polyethyleneimine, polyethyl cyanoacrylate, polyvinylene carbonate, polypropylene carbonate, polyvinyl carbonate, polymalonate substances, polysuccinate substances, polyimide, polyetherimide and polyethersulfone; Preferably, the polymalonate material includes at least one of polypentylene malonate, polyethylene malonate, polypropylene malonate and polyhexylene malonate; Preferably, the polysuccinate material includes polyethylene succinate and / or polypropylene succinate; Preferably, based on the total mass of the shell being 100%, the mass content of the second polymer is 90%-20%, preferably 50%-40%.

3. The nanofiber with a core-shell structure according to claim 1 or 2, characterized in that: The ceramic particles are located on the surface and / or inside of the shell; Preferably, based on the total mass of the shell being 100%, the mass content of the ceramic particles is 10%-80%, preferably 50%-60%; Preferably, in the shell, the ceramic particles include a first inorganic ceramic, and the first inorganic ceramic is a nitride inorganic ceramic; Preferably, the nitride inorganic ceramic includes at least one of boron nitride, aluminum nitride, silicon nitride, titanium nitride and magnesium nitride; Preferably, the boron nitride includes hexagonal boron nitride and / or N-type cubic boron nitride; Preferably, the inorganic ceramic further includes a second inorganic ceramic, and the second inorganic ceramic includes at least one of aluminum oxide, titanium dioxide, silicon dioxide, zirconium dioxide, molybdenum-doped silicon dioxide, zirconium boride, zirconium nitride ceramics, silicon boride, vanadium boride, titanium boride, magnesium boride and an inorganic ceramic solid electrolyte; Preferably, the inorganic ceramic solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lanthanum titanate lithium oxide, tantalum-doped lithium lanthanum zirconium oxide, aluminum-doped lithium lanthanum zirconium oxide, lithium germanium phosphorus sulfur, lithium phosphorus sulfur chloride and lithium germanium aluminum phosphate; Preferably, the mass of the second inorganic ceramic accounts for 0-95% of the mass of the first inorganic ceramic and does not include 0%.

4. The nanofiber with a core-shell structure according to any one of claims 1 to 3, characterized in that: The shell also includes a one-dimensional material toughening agent; Preferably, in the shell, the mass ratio of the one-dimensional material toughening agent to the ceramic particles is 1:(5-10); Preferably, the one-dimensional material toughening agent is selected from at least one of a one-dimensional inorganic material and a one-dimensional organic material; Preferably, the one-dimensional inorganic material comprises at least one of aluminum oxide fiber, silicon dioxide fiber, zirconium dioxide fiber, boron nitride fiber, boron nitride nanotube, glass fiber, titanium dioxide nanotube and zirconium dioxide nanotube; Preferably, the mass proportion of the one-dimensional inorganic material in the one-dimensional material toughening agent is 50%-100%; Preferably, the one-dimensional organic material comprises at least one of nylon fiber, polyvinylidene fluoride fiber, polyimide fiber, polyphenylene sulfide fiber, polyvinylidene fluoride-hexafluoropropylene fiber and polyvinylidene fluoride-chlorotrifluoroethylene fiber; Preferably, the mass proportion of the one-dimensional organic material in the one-dimensional material toughening agent is 0%-50%.

5. The nanofiber with a core-shell structure according to any one of claims 1 to 4, characterized in that: The diameter of the nanofibers with core-shell structure is 1 μm-5 μm; Preferably, the diameter of the polymer fiber core is 500nm-2μm; Preferably, the particle size of the ceramic particles is 10 nm-500 nm, preferably 50 nm-300 nm.

6. A method for preparing a nanofiber having a core-shell structure according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: dissolving a first polymer in a first organic solvent to obtain a solution A; adding a second polymer and ceramic particles into a second organic solvent to obtain a dispersion B; Among them, the preparation of solution A and dispersion B is in no particular order; Solution A and dispersion B are used to prepare the nanofibers with a core-shell structure by using a coaxial electrospinning method or a melt-blowing method.

7. The method for preparing nanofibers with a core-shell structure according to claim 6, characterized in that: The first organic solvent comprises at least one of toluene, benzene, chloroform, paraffin, petroleum ether and mineral oil; Preferably, during the preparation of solution A, the temperature is raised to above 70°C during dissolution; Preferably, the second organic solvent comprises at least one of nitrogen methyl pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, acetone and ethanol; Preferably, during the preparation of the dispersion B, the material added to the second organic solvent also includes a one-dimensional material toughening agent.

8. The method for preparing nanofibers with a core-shell structure according to claim 6 or 7, characterized in that: When the nanofibers with a core-shell structure are prepared by a coaxial electrospinning method or a melt-blowing method, the dew point of the environment is less than -30°C; Preferably, during the coaxial electrospinning process, the voltage range is 5 kV-22 kV; Preferably, during the coaxial electrospinning process, the distance from the receiving plate to the needle is 13 cm-25 cm.

9. A diaphragm, characterized in that: The diaphragm comprises the nanofiber with a core-shell structure as described in any one of claims 1 to 5, or comprises the nanofiber with a core-shell structure prepared by the method described in any one of claims 6 to 8.

10. A battery comprising a positive electrode, a negative electrode and a separator, wherein the separator is located between the positive electrode and the negative electrode to isolate the positive electrode from the negative electrode, characterized in that: The diaphragm is the diaphragm according to claim 9; Preferably, the battery is an all-solid-state battery or a semi-solid-state battery; Preferably, a flexible interface is formed between the separator and the positive electrode and / or between the separator and the negative electrode.

Citation Information

Cited By

  • Mixed glass fiber storage battery diaphragm and diaphragm manufacturing method and system

    CN121484380A